Performance of Multipurpose Plants as Plant Enrichment in Community Managed Forest in Karang Sidemen Village, Central Lombok - Idris, Muhamad Husni; Setiawan, Budhy; Aji, Irwan Mahakam Lesmono Aji; Chaerani, Nurul (Jurnal Biologi Tropis, 2025)
Forest areas enrichment with multipurpose plants could increase the success of forest area management by the community. This study describes the performance of multipurpose trees as plant enrichment in community managed forest in Karang Sidemen Village, Central Lombok, and to analyze the factors that influence it. Data were collected in August 2023. Respondents were farmers who received plant enrichment assistance in 2017 sponsored by the Millennium Challenge Account Indonesia (MCAI). Vegetation data were collected from 36 sample plots of 20x20m with subplots of 10x10m and 5x5m. The results showed that the enrichment plants found were avocado, durian, mangosteen and langsat, with the population of 157 individuals/ha (5% of stem diameters (f) 10-<20cm and 96% of f 2-<10cm), which was less than that of banana population of 466 individuals/ha. The population without banana was 1383 individuals/ha with 5.93%, 45.86% and 89.66% belong to f >=20cm, 10-<20cm and 2-<10cm, respectively. The average f at 120cm height for enrichment plants of avocado, durian, mangosteen and langsat were 6.16cm, 5.48cm, 4.26cm and 3.77cm respectively, while the average plant height was 5.26m, 4.07m, 2.39m and 4.86 m respectively. Low soil organic content and dense plant populations tend to result in smaller diameters of multipurpose plants.